Desigualdade sócio-espacial e violência urbana: a região metropolitana da Grande Vitória - Mattos, Rossana Ferreira da Silva (2008)
The present analyzes how the economic and social changes occurred in the country as of the 80 s changed the social-spatial setting standard, contributing to the increase of urban violence in the Metropolitan Region of Great Vitória, in the context of productive restructuring and consequent changes in labor market. It has as main hypothesis the deepening of the segregation which may lead to the social fragmentation, and, as consequence, generate a social environment not so favorable to the construction of convention strategy and create an environment that stimulates the urban violence. It analyzes also the dynamic of the metropolitan space organization, associating the same with the social-spatial structure transformations. Such approach is developed as from the evaluation, in 2000, on how the local dynamics specificities, compared to the macro-economical determinations, interfere in the segregation and the urban violence board. This way, the intensification of labor precariousness, of segregation and urban violence is observed